An integrated geophysical study of the quaternary basin at Olak Lempit-Banting Area, Selangor, Malaysia = Kajian geofizik bersepadu lembangan kuaterneri di kawasan Olak Lempit-Banting, Selangor, Malaysia - Abdul Rahim Samsudin; Umar Hamzah; Zuraidah Ramli (Universiti Kebangsaan Malaysia, 2007)
An integrated geophysical study was conducted to investigate the subsurface regional structure and the presence of a Quaternary sedimentary basin in the Olak Lempit - Banting area of Selangor, Malaysia. A regional gravity survey and the high resolution reflection seismic were employed to determine the thickness and areal distribution of the alluvial sedimentary basin as well as to investigate the depth and topography of the bedrock in the study area. The sedimentary basin hosts one of the most important coastal alluvial aquifer which was used to cater the shortage of domestic water supply during the worst water crisis that hit the state of Selangor in 1998. The surface geological map shows that in general 70% of the study area is covered by Quaternary deposits of Beruas, Gula and Simpang Formations which overlie the sedimentary bedrock of Kenny Hill Formation. The Beruas Formation consists of mainly clay, sandy clay and peat of Holocene fluviatile-estuarine deposits, whereas the Gula Formation represents Holocene marine to estuarine sediments which mostly consists of clay and minor sand. The Simpang Formation (Pleistocene) is a continental deposit comprising of gravel, sand, clay and silt. The underlying Kenny Hill Formation consists of a monotonous sequence of interbedded shales, mudstones and sandstones. The rock is Carbonaceous in age and it forms an undulating surface topography in the eastern part of the study area. A total of 121 gravity stations were established using a La Coste & Romberg gravity meter and the elevations of most of the stations were determined barometrically using Tiernan-Wallace altimeters. The high resolution seismic reflection using the common mid point (CMP) or roll along technique was carried out using a 24 channel signal enhancement seismograph and high frequency geophones. A total length of about 1.7 km stacked seismic section has been acquired in this survey and a nearby borehole data was used for interpretation. A relative Bouguer anomaly map shows an elongated zone of low gravity anomaly trending approximately NW-SE which is interpreted to be the deposition center of the Quaternary basin. The interpreted gravity profiles running across the central area of the study area show that the basin has thickness varies from tenth to several hundred meters with maximum depth to bedrock of about 275 m. A gravity profile which passes through the eastern edge of the basin was modeled with depth to bedrock of about 178 m below ground which agrees very well with those obtained from the interpreted seicmic section and borehole data. The stacked seismic section shows several high amplitude parallel to sub-parallel reflection overlying discontinuos and low reflection pattern. Reflections on the eastern part of the section is much shallower than the one observed on the western part which clearly indicates the presence of basinal structure with a total interpreted depth to bedrock of about 200 meters.